Estimation of Salivary and Tissue Nitric Oxide Levels in Oral Squamous Cell Carcinoma: A Biochemical Study: Salivary and Tissue Nitric Oxide - Ghosh, Rumela; Castelino, Renita Lorina; Babu, Subhas G; Banerjee, Baishwanar (European Journal of Therapeutics, 2021)
Objective: The study was conducted to estimate the salivary and tissue nitric oxide (NO) levels in healthy individuals and subjects with squamous cell carcinoma of the oral cavity. Methods: In this study, the salivary and tissue NO levels were estimated in 20 healthy subjects and 20 patients with oral squamous cell carcinoma (OSCC). Results: The mean salivary NO levels in Group I (control group) was 78.59 μM/L (standard deviation=5.91608), while the mean salivary NO levels of Group II (study group) were 115.6765 μM/L (standard deviation=0.9431). The mean tissue NO levels in Group I (control group) was 87.6315 μM/L (standard deviation=1.91631), while the mean tissue NO of Group II (study group) was 172.376 μM/L (standard deviation=0.84774. Conclusion: Our results illustrated that the increase in the NO levels in the saliva is positively correlated with the NO level in tissues; hence, salivary NO level can be used as a potential diagnostic biomarker in OSCC.